Longitudinal Quantification of Eye-Movement Impairments after Pontine Hemorrhage - Suner, Melis; Prusky, Glen T.; Carmel, Jason B.; Hill, N. Jeremy (Frontiers in Neurology, 2017)
INTRODUCTION: We report a case of hypertrophic olivary degeneration due to pontine hemorrhage. A 59-year-old male with untreated hypertension suffered a primary pontine hemorrhage which caused horizontal eye movement limitation. Progressive neurological deterioration with involuntary eye and palatal movements began months after hemorrhage. This was accompanied by MRI evidence of hypertrophic olivary degeneration at 4.5 months. BACKGROUND: Primary pontine hemorrhage often leads to impairment of eye movements, and diplopia. Hypertrophic olivary degeneration can also emerge months after hemorrhage, producing involuntary pendular eye movements. Neither the natural history of voluntary eye movements nor the emergence of involuntary eye movements after pontine hemorrhage has been previously quantified. METHODS: We used an optokinetic task that enabled measurement of eye movements. It provided real-time feedback on the ability to track continuously and saccade quickly in a pursuit task. The feedback motivated the patient to use the system repeatedly in his home. From three months after hemorrhage, the patient used the system for nine months, allowing us to quantify changes in his eye movements. RESULTS: Horizontal gaze impairments were manifest in our task as limitation in horizontal range of motion, as well as delay in initiation of the right eye’s movement during left-to-right pursuit. Improvement in these impairments was measured over the course of months 3-7 post hemorrhage. In addition, the emergence of vertical pendular nystagmus was identified in the subject at 4.0 months. Analysis of the eye-movement records revealed pre-symptomatic oscillatory eye movements whose amplitude had grown steadily over the course of three weeks, prior to a sharp increase in amplitude that coincided with the patient's first report of oscillopsia. Horizontal pendular nystagmus emerged 7.4 months after the hemorrhage, primarily in the left eye. CONCLUSION: An eye-tracking system deployed in a patient’s home enabled prospective longitudinal quantification of the natural history and improvement in voluntary eye movement impairments after pontine hemorrhage. It also characterized prospectively for the first time, the emergence of involuntary eye movements resulting from the rare complication of hypertrophic olivary degeneration. Results suggest that brief weekly measurements with an eye-tracker may allow early detection of this complication.